2018
DOI: 10.1159/000493762
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Self-Limited Acute Pancreatitis Cases at Admission to Emergency Unit

Abstract: Background: While acute pancreatitis (AP) resolves spontaneously with supportive treatment in most patients, it may be life-threatening. Predicting the disease severity at onset dictates the management strategy. We aimed to define the patients with mild pancreatitis who may be considered for outpatient management with significant cost-savings. Materials and Methods: This prospective observational study included 180 patients with mild AP according to the harmless acute pancreatitis score (HAPS) and Imrie score.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…We have not assessed the validity and reliability of that system, however, we feel that any patient with AP having NL ratio of less than 4.7 at admission, Glasgow score less than 2, CRP of less than 150-190 at 48 hours, and rise in CRP of less than 90 in 48 hours will have more than 80% chances of not developing the complicated acute pancreatitis. The clinical implication is that such patients can be discharged earlier or can be managed on ambulatory care basis [24]. In patients with high suspicion of the severity of the disease, a CT scan should be performed and MCTSI should be calculated.…”
Section: Discussionmentioning
confidence: 99%
“…We have not assessed the validity and reliability of that system, however, we feel that any patient with AP having NL ratio of less than 4.7 at admission, Glasgow score less than 2, CRP of less than 150-190 at 48 hours, and rise in CRP of less than 90 in 48 hours will have more than 80% chances of not developing the complicated acute pancreatitis. The clinical implication is that such patients can be discharged earlier or can be managed on ambulatory care basis [24]. In patients with high suspicion of the severity of the disease, a CT scan should be performed and MCTSI should be calculated.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, Kayar et al (29) assessed 180 patients with AP and mild pancreatitis with the aim of identifying patients who should be considered for home-monitoring. The results from a previous study indicated that there were no significant alterations in the CT findings of mild AP patients at 12 and 72 h (29). Another previous study assessed the role of low molecular weight heparin in the management of patients with moderately severe AP (MSAP) (30).…”
Section: Discussionmentioning
confidence: 99%
“…During this time, a pro-inflammatory sterile response occurs, which can lead to systemic inflammatory response syndrome (SIRS)[ 13 ]. Nevertheless, AP is self-limited in more than 80% of patients, and treatment in the early phase consists of supportive care instead of a curative intervention[ 14 ]. However, necrosis and acute necrotic collection (ANC) can occur in the late phase.…”
Section: Phases Of Apmentioning
confidence: 99%